Patterns and correlates of attempted suicide amongst heroin users: 11-year follow-up of the Australian treatment outcome study cohort. Issue 2 (30th June 2015) - Darke, Shane; Ross, Joanne; Marel, Christina; Mills, Katherine L.; Slade, Timothy; Burns, Lucy; Teesson, Maree
Abstract: Lifetime and recent rates of attempted suicide and suicidal ideation amongst the Australian Treatment Outcome Study cohort of heroin users at 11-year follow-up were examined. The mean elapsed time since heroin initiation was 20.4 years. At 11-year follow-up, 42.2% of the cohort reported ever having made a suicide attempt, 11.1% having made a first attempt subsequent to baseline. In the year preceding 11-year follow-up, 1.6% had made an attempt, suicidal ideation was reported by 10.4%, and 4.2% had a current suicide plan. After controlling for other variables, past 12 month attempts, current ideation or plans were independently associated with a current diagnosis of Major Depression (odds ratios (OR) 1.67) and more extensive polydrug use (OR 1.39), while each standard deviation higher on the SF12 physical health scale (reflecting better health) was associated with reduced odds (OR 0.66). Suicide and suicidal ideation remained a significant clinical issue for heroin users, some 20 years after their heroin use commenced. Highlights: Attempted suicide and ideation amongst heroin using cohort examined at 11 year follow-up. Mean elapsed time since heroin initiation was 20.4 years. 42.2% had made an attempt. In preceding year, 1.6% had attempted, suicidal ideation reported by 10.4%. Independent correlates were Major Depression, polydrug use, poorer physical health.